Secrets of underground London [videorecording (DVD)] - Scala, Gareth; West, Samuel, 1966- (Pioneer Productions, 2014)
On the surface, London is a buzzing, modern metropolis. But underneath lies a secret, hidden world, all but forgotten by the millions of people above. Secrets of Underground London uncovers 2000 years of subterranean history: a world of ancient caves and perfectly preserved Roman remains; mysterious rivers and gruesome plague pits; impenetrable vaults and top-secret bunkers.